ONTOLOGI, EPISTEMOLOGI DAN AKSIOLOGI PENDIDIKAN PESANTREN PADA ERA MODERN - Abd. Muqit; Shokhibul Mighfar (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2020)
The ontology of pesantren education is to build the lives of the student with Islamic values because the contents of pesantren education are Islamic doctrine. The epistemology of pesantren education is a method/approach to develop education in pesantren, so that in its axiological aspect can creating individuals who are noble, removes the paradigm of the dichotomy of science, changes indoctrination into participatory, builds a theoretical approach towards an applicative approach, combining a harmonious relationship between reason and revelation, useful knowledge, scientific charity, piety, and noble. The education of pesantren in the modern era needs to prepare learning media to support the achievement of educational goals. In the perspective of Islam, the universe is a medium of learning, included in this category is the media of technology. It’s just that the role of the teacher needs to be prioritized so there is no dehumanization in education.